Hepatitis C elimination among people who inject drugs: Challenges and recommendations for action within a health systems framework. (22nd September 2018) - Day, Emma; Hellard, Margaret; Treloar, Carla; Bruneau, Julie; Martin, Natasha K.; Øvrehus, Anne; Dalgard, Olav; Lloyd, Andrew; Dillon, John; Hickman, Matt; Byrne, Jude; Litwin, Alain; et al.
Abstract: The burden of hepatitis C infection is considerable among people who inject drugs (PWID), with an estimated prevalence of 39%, representing an estimated 6.1 million people who have recently injected drugs living with hepatitis C infection. As such, PWID are a priority population for enhancing prevention, testing, linkage to care, treatment and follow‐up care in order to meet World Health Organization (WHO) hepatitis C elimination goals by 2030. There are many barriers to enhancing hepatitis C prevention and care among PWID including poor global coverage of harm reduction services, restrictive drug policies and criminalization of drug use, poor access to health services, low hepatitis C testing, linkage to care and treatment, restrictions for accessing DAA therapy, and the lack of national strategies and government investment to support WHO elimination goals. On 5 September 2017, the International Network of Hepatitis in Substance Users (INHSU) held a roundtable panel of international experts to discuss remaining challenges and future priorities for action from a health systems perspective. The WHO health systems framework comprises six core components: service delivery, health workforce, health information systems, medical procurement, health systems financing, and leadership and governance. Communication has been proposed as a seventh key element which promotes the central role of affected community engagement. This review paper presents recommended strategies for eliminating hepatitis C as a major public health threat among PWID and outlines future priorities for action within a health systems framework.